Pengaruh Kualitas Produk Terhadap Loyalitas Pelanggan Pada PT Kerta Laksana Cimahi – Jawa Barat - Naim, Naim; Hamali, Arif Yusuf (STIE Ekuitas, 2020)
This research was conducted at PT Kerta Laksana Cimahi – West Java, aimed to know the correlation of product quality and customer loyalty, and also to analyze the influence of product quality to customer loyalty at PT Kerta Laksana Cimahi – West Java. Respondents of this research are 26 selected using saturated sample or census technique. The method use is descriptive and associative, which tests the influence of dependent and independent variables using Pearson Product Moment correlation analysis, and also done to determine the accuracy of measurement using validity and reliability test. Result of the validity and reliability test of variables X and Y express all valid and reliable. The result showed that product quality at PT Kerta Laksana Cimahi – West Java is in the category of good and customer loyalty is in the category of good. Result of the research showed that there is the correlation of product quality to customer loyalty at PT Kerta Laksana Cimahi – West Java, and based on the interpretation of Pearson Product Moment correlation, this relationship is in the criteria of strong. The result showed that the hypothesis is proved: there is the influence of product quality to customer loyalty at PT Kerta Laksana Cimahi – West Java. Keywords: Product Quality; Customer Loyalty.